The association between chronic psychological stress and uterine fibroids risk: A meta‐analysis of observational studies. (5th September 2019) - Qin, Hao; Lin, Zhijuan; Vásquez, Elizabeth; Xu, Luo
Abstract: The association between chronic psychological stress and uterine fibroids (UFs) risk remains unclear. In this study, a meta‐analysis of observational studies was performed to explore the reported association between them. A literature search was performed in PubMed, EMBASE, and Web of Science to identify relevant published articles. A random‐effect model was used to examine pooled odds ratio (OR) and 95% confidence interval (CI). Additionally, subgroup analyses and two‐stage random‐effect dose–response meta‐analysis were performed. A total of six articles with seven studies were included in this meta‐analysis. For the highest versus lowest category of chronic psychological stress, the pooled OR was 1.24 (95% CI [1.15, 1.34]; p = .000). Through subgroup analyses, we found a positive association between chronic psychological stress and UFs risk especially in non‐Hispanic Blacks studies (OR, 1.24, 95% CI [1.14, 1.34], p = .000). When evaluating for a dose–response, we found a weak correlation between chronic psychological stress and UFs risk, especially for the severe (OR, 1.17, 95% CI [1.07, 1.29]) and very severe (OR, 1.23, 95% CI [1.07, 1.41]) categories. Our meta‐analysis shows a statistically significant association between chronic psychological stress and UFs risk particularly for non‐Hispanic Blacks. Interventions aiming to reduce chronic psychological stress may be useful to decrease the prevalence of UFs.